2003
DOI: 10.1074/jbc.c200634200
|View full text |Cite
|
Sign up to set email alerts
|

Coactivator PRIP, the Peroxisome Proliferator-activated Receptor-interacting Protein, Is a Modulator of Placental, Cardiac, Hepatic, and Embryonic Development

Abstract: Nuclear receptor coactivator PRIP (peroxisome proliferator-activated receptor (PPAR␥)-interacting protein) and PRIP-interacting protein with methyltransferase activity, designated PIMT, appear to serve as linkers between cAMP response element-binding protein-binding protein (CBP)/p300-anchored and PBP (PPAR␥-binding protein)-anchored coactivator complexes involved in the transcriptional activity of nuclear receptors. To assess the biological significance of PRIP, we disrupted the PRIP gene in mice by homologou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
69
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(75 citation statements)
references
References 40 publications
6
69
0
Order By: Relevance
“…Chimeric male mice derived from C57BL/6 blastocysts and NRC ϩ/Ϫ embryonic stem (ES) cells (129S6 background) were crossed with C57BL/6 females to obtain NRC ϩ/Ϫ mice in a mixed background (indicated as C57/129). As previously reported, the NRC Ϫ/Ϫ mutation is embryonic lethal and no NRC Ϫ/Ϫ mice are born while NRC ϩ/Ϫ mice in the mixed C57/129 background are viable and able to reproduce (2,32,73). We have observed these NRC ϩ/Ϫ mice over a 2-year period and have noted that they develop an interesting phenotype associated with chronic wound healing.…”
supporting
confidence: 72%
See 3 more Smart Citations
“…Chimeric male mice derived from C57BL/6 blastocysts and NRC ϩ/Ϫ embryonic stem (ES) cells (129S6 background) were crossed with C57BL/6 females to obtain NRC ϩ/Ϫ mice in a mixed background (indicated as C57/129). As previously reported, the NRC Ϫ/Ϫ mutation is embryonic lethal and no NRC Ϫ/Ϫ mice are born while NRC ϩ/Ϫ mice in the mixed C57/129 background are viable and able to reproduce (2,32,73). We have observed these NRC ϩ/Ϫ mice over a 2-year period and have noted that they develop an interesting phenotype associated with chronic wound healing.…”
supporting
confidence: 72%
“…The following findings summarize these results. CBP Ϫ/Ϫ , p300 Ϫ/Ϫ , TRAP220 Ϫ/Ϫ , and NRC Ϫ/Ϫ mice are embryonic lethal (2,20,26,32,33,57,68,73). TRAP220 ϩ/Ϫ mice are viable but exhibit pituitary hypothyroidism.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…We and others have shown that inactivation of both of the AIB3 alleles in mice results in embryonic lethality due to defects in placental, cardiac, and hepatic development (23)(24)(25). These phenotypes are similar to those encountered in mice lacking PPAR␥ or PPAR␥-binding protein (26,27).…”
Section: Introductionsupporting
confidence: 56%